The Religious Court Trial Of Wali Adhal Cases In The Indonesian Legal System: A Legal Analysis - Mardi Candra; Ramlani Sinaulan; Fahadil Al Hasan; Jelang Ramadhan (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2023)
Marriage combines the husband-wife relationship and unifies two families of different ethnicities, cultures, and backgrounds. The consent of the wali is a significant function of the family, particularly the prospective bride's family. Marriage requires the permission of the wali because it is null and void without it. In actuality, the wali of the prospective bride may be hesitant to marry off the woman under his supervision for various reasons, both Shar'i and non-Shar'i. As a result, the prospective bride must apply to the Religious Court for wali adhal for the marriage to occur. This qualitative research employs a normative legal approach, which examines legal norms found in laws and regulations, judge judgments, and other legal sources. According to the findings of this study, wali adhal cases are currently evaluated by voluntary trials or unilaterally. However, because it is unilaterally assessed and there is no opponent, fulfilling the legal purpose of building integrative justice in this examination requires considerable effort. Therefore, wali adhal cases must be examined using a contentious trial.